2023
DOI: 10.1002/cncr.35000
|View full text |Cite
|
Sign up to set email alerts
|

Increasing risk of hepatocellular carcinoma with successive generations in the United States among Mexican American adults: The Multiethnic Cohort

Nicholas Acuna,
Kali Zhou,
Paulo S. Pinheiro
et al.

Abstract: BackgroundUS‐born Latinos have a higher incidence of hepatocellular carcinoma (HCC) than foreign‐born Latinos. Acculturation to unhealthy lifestyle behaviors and an immigrant self‐selection effect may play a role. In this study, the authors examined the influence of generational status on HCC risk among Mexican American adults.MethodsThe analytic cohort included 31,377 self‐reported Mexican Americans from the Multiethnic Cohort Study (MEC). Generational status was categorized as: first‐generation (Mexico‐born;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…This increased risk among US-born adults is well documented[ 21 25 ] and thought to be multifaceted and driven by factors such as increased uptake of behaviors known to increase cancer risk. A recent study by Acuna et al found significant increases in HCC risk among successive generations of Mexican Americans after controlling for lifestyle factors, history of diabetes, neighborhood socioeconomic status, and ethnic enclave[ 24 ]. Sex-stratified analyses by Acuna et al and others have revealed that increases in risk among US-born Hispanic populations appear to only occur for males, a finding that may help pinpoint drivers of differences in risk by nativity[ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This increased risk among US-born adults is well documented[ 21 25 ] and thought to be multifaceted and driven by factors such as increased uptake of behaviors known to increase cancer risk. A recent study by Acuna et al found significant increases in HCC risk among successive generations of Mexican Americans after controlling for lifestyle factors, history of diabetes, neighborhood socioeconomic status, and ethnic enclave[ 24 ]. Sex-stratified analyses by Acuna et al and others have revealed that increases in risk among US-born Hispanic populations appear to only occur for males, a finding that may help pinpoint drivers of differences in risk by nativity[ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Acuna et al found significant increases in HCC risk among successive generations of Mexican Americans after controlling for lifestyle factors, history of diabetes, neighborhood socioeconomic status, and ethnic enclave[ 24 ]. Sex-stratified analyses by Acuna et al and others have revealed that increases in risk among US-born Hispanic populations appear to only occur for males, a finding that may help pinpoint drivers of differences in risk by nativity[ 23 , 24 ]. Our results also showed that disparities in HCC incidence by ethnicity exist among foreign-born adults, likely due to the relatively high rates of liver cancer in Mexico driven etiologically by alcoholic liver disease, hepatitis C virus, increasingly, non-alcoholic steatohepatitis[ 26 ].…”
Section: Discussionmentioning
confidence: 99%